Understanding factors influencing vaccination acceptance during pregnancy in Hackney, London. (November 2016) - Wilson, Rose Jane; Larson, Heidi; Paterson, Pauline
Abstract: Background: In England, influenza immunisation was first recommended to all pregnant women in 2009, and in response to a pertussis outbreak in 2012 the UK Department of Health introduced pertussis vaccination for all pregnant women. The aim of this study was to gain a contextualised understanding of factors influencing acceptance of vaccination during pregnancy in Hackney, a borough in north-east London, UK. Hackney was chosen because it has one of the lowest vaccination coverage rates in pregnancy in the UK. Methods: A purposive sampling method was used to recruit 40 pregnant and recently pregnant women from a wide range of backgrounds, and ten health-care professionals, from three general practices, two community antenatal clinics, nine parent-toddler groups, and four community centres. In-depth interviews and a focus group discussion with pregnant and recently pregnant women explored experiences of National Health Service health care during pregnancy and their views about vaccination in pregnancy. In-depth interviews with health-care workers explored their views about vaccination in pregnancy and how they discuss and provide vaccination. Interview and focus group data were analysed both inductively and deductively with a thematic analysis approach. Findings: The overarching themes relating to vaccine hesitancy identified from the interviews with pregnant and recently pregnant women were perceived risks associated with vaccination or the diseases they aim to prevent, trust in health-care workers and vaccination, and social influence. In addition to vaccine hesitancy, reasons for not being vaccinated, especially among women of lower socioeconomic status, included lack of access to vaccination or vaccination not having been recommended by a health-care worker. Overarching themes identified from the interviews with health-care workers were trust in vaccination, perceived importance of vaccination, responsibility of vaccine administration, perceived patient concerns, and interaction with patients. Interpretation: Reasons for vaccine hesitancy are complex. The findings of this study indicate that advice from friends, family, and the internet can greatly influence a pregnant woman's vaccination decisions. Hesitancy can be exacerbated because attitudes about vaccination and provision vary among health-care workers in Hackney. Also there are certain barriers to accessing vaccinations among patients of lower socioeconomic status. The results will help to inform contextualised policies aimed at increasing vaccination uptake and reducing inequality in access to vaccination during pregnancy in Hackney. Funding: National Institute for Health Research (NIHR) Health Protection Research Unit in Immunisation at the London School of Hygiene & Tropical Medicine (LSHTM) in partnership with Public Health England (PHE).